INTERPERSONAL MEANING COMPLEMENTARITY BETWEEN SONG LYRICS AND ITS COVER: A MULTIMODALITY ANALYSIS OF TEXT AND IMAGE - Adhitya Alfian; Khristianto (Arkhais - Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
This article is aimed to give contributions to studies and increase knowledge the liguistics of Indonesian music scene. This study examines the meaning of the interpersonal approach of intersemiotic Complementarity (Royce. 2001) which believes that both images and text in one text are a unity and convey a complementary meaning. Intersemiotic Complementarity combines two frameworks between SFL by Halliday (1994) and Multimodal Discourse by Kress and Leeuwen (1996). Based on the analysis, interpersonal meaning which contained in verbal mood of Omnipotence Paradox – Eternal Desolator consists of declarative and interrogative mood. Declarative mood dominates the lyrics that provides spiritual statements regarding the existence of God. The speaker also gives information to listeners that the lyrics are in essence not solely created by the speker but also come from the demons whispered who tries to ruined humans believe in their god. Through the interrogative modes, demons tries to ask polarizing questions that ask the author's divinity so that he gets trapped in the demon's perception. Meanwhile, the visual meaning of his digital artwork is to try to represent the lyrics into a low modality image that was made unclear by combining various references to divine images that are spread across social phenomenon.